2006
DOI: 10.1001/archpsyc.63.7.778
|View full text |Cite
|
Sign up to set email alerts
|

Association Testing of the Positional and Functional Candidate Gene SLC1A1/EAAC1 in Early-Onset Obsessive-compulsive Disorder

Abstract: The 3' region of SLC1A1 may contain a susceptibility allele for early-onset OCD, with differential effects in males and females. The results also provide further support for the involvement of a glutamatergic dysfunction in the pathogenesis of early-onset OCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
193
2
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 263 publications
(211 citation statements)
references
References 55 publications
15
193
2
1
Order By: Relevance
“…It should also be noted that the recent association between 5-HTTLPR and OCD by Hu et al was observed in a case-control as well as in a family-based association study, the latter of which is not susceptible to hidden population stratification. Thus, the lack of association in our study warrants further analyses in large family-based OCD samples such as the OCD Collaborative Genetics Study ) before it will point toward the need to analyze other candidate regions such as 9p, 3q, 7p, 1q, 15q, 6q, and 13q (Hanna et al, 2002;Shugart et al, 2006;Willour et al, 2004) and polymorphisms involved in other neurotransmitters such as glutamate (Arnold et al, 2006;Dickel et al, 2006;Rosenberg and Keshavan, 1998), neuromodulators, and developmental signals potentially of importance in OCD such as glutamate.…”
Section: Discussionmentioning
confidence: 84%
“…It should also be noted that the recent association between 5-HTTLPR and OCD by Hu et al was observed in a case-control as well as in a family-based association study, the latter of which is not susceptible to hidden population stratification. Thus, the lack of association in our study warrants further analyses in large family-based OCD samples such as the OCD Collaborative Genetics Study ) before it will point toward the need to analyze other candidate regions such as 9p, 3q, 7p, 1q, 15q, 6q, and 13q (Hanna et al, 2002;Shugart et al, 2006;Willour et al, 2004) and polymorphisms involved in other neurotransmitters such as glutamate (Arnold et al, 2006;Dickel et al, 2006;Rosenberg and Keshavan, 1998), neuromodulators, and developmental signals potentially of importance in OCD such as glutamate.…”
Section: Discussionmentioning
confidence: 84%
“…This is equivalent to overtransmission of the C allele under the dominant model. A haplotype previously identified for association with OCD [Dickel et al, 2006], including this SNP (rs301430-rs301979), was also significant under a recessive model. The T-G haplotype type was undertransmitted to individuals with autism.…”
Section: Discussionmentioning
confidence: 68%
“…Dickel et al [2006] reported that two of the nine SNPs they tested, including rs3780412 from the Arnold paper (P 5 0.04) and rs301430, which showed significant overtransmission of the C allele (P 5 0.03), were significantly associated with OCD. Only rs3780412 was associated with OCD when they restricted their sample to males only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations